Business Development Strategy in Telecommunication Company at PT XYZ - Febrianto H Masigi; Siti Jahroh; Arry Ekananta (Pelopor Publikasi Akademika, 2024)
The rapid and dynamic growth of the telecommunications and information industry in the era of Society 5.0 presents significant challenges for telecommunication providers, including PT XYZ, a leading telecommunications service company in Indonesia. This study aims to analyze internal and external factors affecting PT XYZ's business revenue, formulate alternative strategies, and prioritize business strategies to address challenges and enhance revenue. Using qualitative methods, data collection involved observation, interviews, surveys, and literature reviews, drawing from primary and secondary sources. The study employed SWOT, PESTLE, and Porter’s Five Forces analyses to evaluate the company’s environment comprehensively. Findings indicate that PT XYZ is positioned in cell I (Grow and Build) in the IE matrix, with IFE and EFE scores of 3.851 and 3.0, respectively. Recommended strategies include market penetration, product development, and integrative strategies such as ERP implementation to enhance operational efficiency and adapt to technological changes. The study underscores the importance of creating a diverse portfolio of customer-driven technology products and expanding market reach while adopting effective risk management practices. These strategies are expected to sustain PT XYZ’s competitive position and drive revenue growth in the telecommunications industry.